Adverse Effects and Toxicity of Immune Checkpoint Inhibitors For Patients With Urothelial Carcinoma - Wang, Di; Sun, Kai; Wang, Tianqi; Zhang, Dongxu; Sun, Fengze; Cui, Yuanshan; Zhao, Hongwei; Wu, Jitao (Frontiers in Pharmacology, 2021)
Urothelial carcinoma (UC) occupies a high incidence among all the genitourinary malignancies. Immune checkpoint inhibitors (ICIs), as alternative treatments of metastatic urothelial carcinoma (mUC), have been applied in the treatment of mUC after chemotherapy failure, with comparable efficacy and safety. ICIs can enhance anti-tumor T cell reactivity and promote immune control over the cancerous cells by blocking cytotoxic T-lymphocyte antigen 4 (CTLA-4) or the combination of PD-1 and PD-L1. In the treatment of urothelial carcinoma, ICIs show obvious advantage and can enhance survival rates. However, their adverse effects are gradually manifested with increasing clinical applications. Therefore, we review the adverse effects and toxicity of ICIs in patients with UC, aiming to provide sound theoretical references and therapeutic strategies for their clinical application.